Implementación de un sistema de contabilidad básico en la caja solidaria señor de la Calera de la Provincia Cotopaxi del barrio la Calera en el periodo 2018 - Comina Anchatipan, Byron Alexis (2019)
The present work entitled the implementation of the Basic Accounting System in the Caja Solidaria "SEÑOR DE LA CALERA" of Cotopaxi province of Barrio La Calera 2018, has the problem that the daily records are made manually, the objectives of this research. It is based on knowing the current situation of accounting records to determine the shortcomings and needs, the basic accounting system in order to provide the tool to improve the recording of operations and conduct training to those responsible for the management of the accounting system. The methodology was based on a research in the field, it was summarized in a documentary bibliographic investigation using techniques such as observation and interview and as instruments the observation and interview cards. The obtained results nothing to do with capital for the acquisition of an accounting system, therefore, the design and implementation of a basic accounting system has been proposed, which contains 4 modules, daily records, accounting journal entries, entry of new clients and generation of credits. The provided capacities on the Basic System Basically, in the decision-making, by the partners for the benefit of the Caja Solidaria.